2017
DOI: 10.1007/s11655-017-2416-x
|View full text |Cite
|
Sign up to set email alerts
|

Red yeast rice prevents atherosclerosis through regulating inflammatory signaling pathways

Abstract: RYR has the anti-atherosclerotic and stabilizing unstable plaque effects. The mechanism might be related to the inflflammatory signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…For instance, Wu et al reported that RYR could reduce the plaque size and decrease the serum levels of cholesterol. 27 It is known that Monascus produce a variety of functional secondary metabolites, among which monacolin compounds are marked to cause a reversible competitive inhibition of HMG-CoA reductase. 28 In addition, monacolin K, a major constitute of RYR, is structurally identical to lovastatin, which is the first statin drug to manage plasma lipids and prevent coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Wu et al reported that RYR could reduce the plaque size and decrease the serum levels of cholesterol. 27 It is known that Monascus produce a variety of functional secondary metabolites, among which monacolin compounds are marked to cause a reversible competitive inhibition of HMG-CoA reductase. 28 In addition, monacolin K, a major constitute of RYR, is structurally identical to lovastatin, which is the first statin drug to manage plasma lipids and prevent coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with recent research showing that supplementation with RYR in Apoe −/− mice decreased the plasma levels of IL-6 and TNF-α. 33 In order to elucidate the signal pathway responsible to RYR treatment, we examined the expression of proteins involved in inflammatory signaling pathways. Our results showed that TLR2, TLR4, and MAPK were significantly increased in the model group, whereas treatment with RYR reversed the increase of the three proteins.…”
Section: Discussionmentioning
confidence: 99%
“…An eight-week administration of XZK (600–1,200 mg/kg) to C57BL/6 mice was found to significantly and dose-dependently inhibit vulnerable plaque progression, decrease the plaque area, and suppress lesional endoplasmic reticulum stress (Shen et al, 2017). In another study involving atherosclerotic rats fed a high-cholesterol diet, the oral administration of RYR at 120 mg/kg significantly reduced the plaque size, stabilized the plaque, protected the endothelium, and decreased the number of lipid droplets and cholesterol calculi, and lowered the levels of high sensitivity C-reaction protein (Hs-CRP), IL-6, and TNF-α, suggesting that the anti-atherosclerotic activity of RYR may be related to inflammatory signaling pathways (Wu et al, 2017). The administration of aqueous and ethanol extracts of RYR to homocysteine-treated human aortic smooth muscle cells (HASMCs) (1–160 µg/ml) for 24 h reduced TNF-α-induced metalloproteinase (MMP)-2 and MMP-9 expression.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…According to TCM, AS is a manifestation of the “blood stasis status”, and therefore should be treated with blood-activating drugs. Previous studies suggested that TCM herbs with blood-activating property could exert anti-inflammatory, anti-platelet aggregation, and anti-ischemia effects on AS ( Huang et al, 2011 ; Wang et al, 2015 ; Wu et al, 2017 ). Taoren Honghua drug (THD), based on a classical formula in an ancient book named Su’an Consilia , consists of blood-activating herbs.…”
Section: Introductionmentioning
confidence: 99%